Gestión ambiental en la construcción (2019)
In a construction many expectations are generated between each of the parties involved in the project: community, builders, national entities, district, professionals in the area of planning, environmental authorities, etc. What forces the manager of a construction, to work taking into account the maximum use of available natural resources and build with minimal environmental impact, while responding to each of the needs of social or economic development in its area of influence. Nowadays, the construction sector is of great importance from the economic point of view and at the same time it is one of the ones with the greatest environmental impact, it lacks much knowledge and tools to promote an adequate environmental management in civil works. . For this reason, it is now necessary to provide the construction sector with basic aspects to ensure that the projects generate the minimum negative impact and that above all these can be managed and minimized.